Facile Synthesis of Cu2O Nanocubes and Their Enhanced Photocatalytic Property Assisted by H2O2 - Xu, Juncui; Wang, Hui; Gu, Heyun; Zeng, Chunyan; Yang, Yumei (Asian Journal of Chemistry, 2012)
Well-defined and uniform Cu2O nanocubes with an average edge length of about 170 nm have been successfully synthesized in the absence of any surfactant using home-made CuC2O4 as precursor at room temperature. The composition, structure and morphology of the obtained products have been characterized by X-ray powder diffraction, transmission electron microscope and field-emission scanning electron microscopy. The experimental results demonstrate that the Cu2O nanocubes exhibit enhanced photocatalytic property for high concentration (100 mg/L) of acid fuchsin degradation under UV light in the presence of H2O2. The factors affecting the acid fuchsin photocatalytic degradation have been investigated, such as irradiation, photocatalyst concentration and hydrogen peroxide initial concentration.